Dynamic attentional bias for pictorial and textual food cues in the visual search paradigm. (1st January 2023) - Luo, Changlin; Qiao, Siyuan; Zhuang, Xiangling; Ma, Guojie
Abstract: Previous studies have found that individuals have an attentional bias for food cues, which may be related to the energy level or the type of stimulus (e.g., pictorial or textual food cues) of the food cues. However, the available evidence is inconsistent, and there is no consensus about how the type of stimulus and food energy modulate food-related attentional bias. Searching for food is one of the most important daily behaviors. In this study, a modified visual search paradigm was used to explore the attentional bias for food cues, and eye movements were recorded. Food cues consisted of both food words and food pictures with different energy levels (i.e., high- and low-calorie foods). The results showed that there was an attentional avoidance in the early stage but a later-stage attentional approach for all food cues in the pictorial condition. This was especially true for high-calorie food pictures. Participants showed a later-stage conflicting attentional bias for foods with different energy levels in the textual condition. They showed an attentional approach to high-calorie food words but an attentional avoidance of low-calorie food words. These data show that food-related attentional bias varied along with different time courses, which was also modulated by the type of stimulus and food energy. These findings regarding dynamic attentional bias could be explained using the Goal Conflict Model of eating behavior.